Exploring the potential of Porang (Amorphophallus muelleri B.) as horticultural plants in Bocok Hamlet, Pondokagung Village, Kasembon District, Malang Regency, East Java - Hanik Isnaini; Istiana Kautsarani; Shofil Fikri (Generasi Biologi Indonesia, 2023)
Porang (Amorphophallus muelleri B.) is one of the well-known root crops in Indonesia because it has a lot of benefits and potential. One of the places that have a lot of Porang plantations is Bocok Hamlet, Pondokagung Village, Kasembon Sub-District, Malang Regency. Many people in this hamlet have Porang plantations, but the utilization of this plant is still not as optimal as other communities. Utilization of the potential of porang is still classified as less than optimal. Researchers conducted this research using 4 methods, namely initial surveys, determining research locations, observing morphological characters, and interviewing respondents. Based on the interviews conducted, the researchers found that porang has various potentials in several fields, such as in food, porang is made into several types of food ingredients such as flour. Besides that, many porang were exported to various countries such as Japan, England, and other countries. In addition, this plant also has abundant vitamin content for added nutrition and smooth metabolism.